A CROSS-SECTIONAL STUDY OF INDEX OF ORTHODONTIC TREATMENT NEEDS(IOTN) IN MENTALLY DISABLED CHILDREN IN SPECIAL EDUCATION SCHOOL, MULTAN - Dr Anila Anbreen; Dr Sajal Khan; Dr Muhammad Hamza Nisar; Dr Maira Iqbal (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: High rates of malocclusion are among the major oral health issues that children with mental illnesses like Down syndrome, autism spectrum disorder, and cerebral palsy encounter. These disorders make it difficult to receive dental treatment and affect speech, chewing, and self-esteem. Although the Index of Orthodontic Treatment Need (IOTN) aids in assessing the degree of malocclusion, nothing is known about how well it works in this susceptible,group. Aims and objectives: The purpose of this study was to evaluate the influence of orthodontic treatment on the quality of life of mentally and physically handicapped children by utilizing IOTN to assess their orthodontic treatment needs. Assessing the degree of malocclusion (DHC and AC components), oral hygiene habits, and psychological issues pertaining to dental aesthetics were among the specific goals. Materials and Methods: 100 youngsters (≥12 years old) with mental disabilities—aside from those with non-communicable diseases—were the subjects of a cross-sectional study. Clinical exams (IOTN-DHC and AC) and a structured questionnaire on nutrition, self-perception, and dental hygiene were used to gather data. To guarantee uniformity, examiners were calibrated. To identify treatment needs and related factors, statistical analysis was done. Findings: Of the subjects, 79% needed orthodontic treatment, with 52% having an extreme need. Crossbite (57%), overjet (55%), and missing teeth (60%), were common problems. 80% of people regularly ate sugary snacks, and 65% of people only brushed their teeth once a day, indicating poor oral hygiene. Psychosocial effects were noteworthy, with 20% reporting bullying and 25% reporting low self-esteem as a result of dental appearance. Thirty percent of referred children had unresolved treatment-related problems, despite the fact that fifty-five percent were happy with orthodontic care. Conclusion: Children with mental disabilities require more orthodontic treatment, highlighting the need for easily available, specialized care. Although its aesthetic component necessitates careful interpretation, IOTN is a useful tool. Oral health, appearance, and general quality of life can all be enhanced by attending to these needs. To improve care options for this neglected population, future research should include longitudinal assessments and increase sample numbers.